2010
DOI: 10.1007/s12032-010-9446-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of PET-CT in the differential diagnosis of thymic mass after treatment of patients with lymphoma

Abstract: Thymic hyperplasia is a common phenomenon in both children and young adults after chemotherapy and may explain the finding of a mediastinal mass in patients with malignant lymphoma after complete remission. In the present study, we report 5 cases with malignant lymphoma presenting with a mediastinal mass on CT scan after completion of chemotherapy diagnosed as thymic hyperplasia by PET-CT imaging. We retrospectively analyzed 5 patients who presented with anterior mediastinal masses a median of 4 months (range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In Table 5 Mean SUV t and SUV b of All Groups during Prechemotherapy, End of Chemotherapy, and Postchemotherapy Periods ( 5 ), or in 11.7% ( n = 120) of young adults with malignant testicular teratoma ( 28 ). In addition, we found thymic rebound at 10 months after the end of chemotherapy in children with lymphoma, while others described thymic rebound at 1-8 months after chemotherapy in children with nonHodgkin lymphoma ( 27 ), at 3-6 months after treatment of adults with malignant lymphoma ( 29 ), and at 3-14 months after chemotherapy in adult patients with malignant testicular teratoma ( 28 ). Smith et al ( 30 ) reported a superior mediastinal thymic extension associated with postchemotherapy thymic hyperplasia in 12% of 93 FDG PET/CT examinations.…”
Section: Discussionmentioning
confidence: 60%
“…In Table 5 Mean SUV t and SUV b of All Groups during Prechemotherapy, End of Chemotherapy, and Postchemotherapy Periods ( 5 ), or in 11.7% ( n = 120) of young adults with malignant testicular teratoma ( 28 ). In addition, we found thymic rebound at 10 months after the end of chemotherapy in children with lymphoma, while others described thymic rebound at 1-8 months after chemotherapy in children with nonHodgkin lymphoma ( 27 ), at 3-6 months after treatment of adults with malignant lymphoma ( 29 ), and at 3-14 months after chemotherapy in adult patients with malignant testicular teratoma ( 28 ). Smith et al ( 30 ) reported a superior mediastinal thymic extension associated with postchemotherapy thymic hyperplasia in 12% of 93 FDG PET/CT examinations.…”
Section: Discussionmentioning
confidence: 60%
“…Recently we noticed in one patient at the end of therapy that the post-treatment inflammatory process may result in false-positive findings on diffusion MRI and FDG-PET/CT owing to macrophage proliferation. Diffusion MRI may also help in differentiating anterior mediastinal residual or recurrent tumour from benign thymic rebound, which is common in both children and young adults after chemotherapy [ 23 ] (Fig. 6).…”
Section: Response Assessmentmentioning
confidence: 99%
“…The most important change in the patients’ management was observed in the lymphoma group since the biopsy sites were altered due to the PET results. In a case series on patients with lymphoma, it was suggested that mild 18 F-FDG accumulating lesions in the anterior mediastinal region may indicate benign lesions like thymic hyperplasia even in lymphoma patients ( 14 ). However, in the case of the presence of diagnostic criteria indicating malignancy in lymphoma patients, secondary malignant tumors of the anterior mediastinum have been indicated in previous case reports ( 15 ).…”
Section: Discussionmentioning
confidence: 99%